Establishing an Integration-Energy-Practice Model for Improving Energy Performance Indicators in ISO 50001 Energy Management Systems - Tsung-Yung Chiu; Yung-Yin Tsai; Shang-Lien Lo (Energies, 2012)
Global energy sources are gradually becoming scarce and prices are continually rising. Governments and businesses in various countries are actively developing technologies for energy management and developing new sources of energy. On 15 June 2011, the International Organization for Standardization (ISO) announced the ISO 50001 standard for energy management systems. Organizations and enterprises are confronted with challenges associated with enhancing energy performance indicators, continuing to improve energy consumption efficiency, and managing third-party international certifications. This study conducted cases studies of businesses that have introduced an ISO 50001 energy management system by using an integration-energy-practice model to improve energy performance indicators and to complete the international auditing and certification procedures for ISO 50001 energy management systems. Based on case study results, the achievement rates for annual energy performance indicators increased, thereby enhancing the energy intensity efficiency. Establishing an integration-energy-practice model for introducing an ISO 50001 energy management system can efficiently meet demands for energy performance indicators and pass the international certification for ISO 50001 energy management systems. The proposed model efficiently provides enterprises with methods for developing sustainable energy management. It integrates internal and external technical resources to establish energy technology think tanks, for promoting successful technology and experiences to various sectors, thereby allowing enterprises to integrate energy management, increase energy efficiency, and meet the ISO 50001 international standard for energy management systems.